A constrained adaptive equalization algorithm - He Zhongqiu; Daoben Li; Sun Xiaojun (2004 IEEE 60th Vehicular Technology Conference, 2004)
In this paper, we propose a constrained least mean square error cost function, which is subject to a quadratic function. It is not different from all of the previous ones, such as in (Daoben Li., Beijing Uni. of Posts and Telecom. Press, p.258-266, 1995), for equalization. The implementation algorithm is a derivative of the previous one for this constrained criterion. A performance comparison is shown between the constrained and unconstrained algorithm.